EXPLORING CULTURALLY-BASED EDUCATIONAL GAMES TO HOLISTICALLY DEVELOP EARLY CHILDHOOD MOTOR AND LANGUAGE SKILLS - Abrar, Muhammad; Maulana, Maulana (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2025)
Early Childhood Education (ECE) is a critical stage in laying the foundation for a child’s holistic development, encompassing motor, language, social, and cognitive aspects. Play serves as an effective approach to ECE because it is enjoyable and naturally stimulates various domains of development. This study aims to explore the forms and contributions of educational games based on local culture in developing motor and language skills in early childhood. Using a qualitative approach with an exploratory-descriptive study design, the research was conducted in ECE institutions located in communities where local cultural heritage is still well-preserved. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The results show that traditional games such as engklek, congklak, jump rope, and role-playing based on folklore possess characteristics appropriate to children’s developmental stages namely active, collaborative, and easy to understand. These games effectively stimulate both gross and fine motor skills through varied physical activities, and enhance children's language abilities through dialogue, imitation of expressions, and social interaction during play. The findings highlight the importance of integrating culturally-based educational games into ECE as a pedagogical strategy that not only preserves cultural values but also supports holistic child development. ABSTRAK Pendidikan Anak Usia Dini (PAUD) adalah tahap penting dalam membentuk dasar perkembangan anak secara menyeluruh. Permainan menjadi pendekatan efektif karena bersifat menyenangkan dan mampu menstimulasi aspek motorik, bahasa, sosial, dan kognitif secara alami. Penelitian ini bertujuan untuk mengeksplorasi bentuk dan kontribusi permainan edukatif berbasis budaya lokal dalam mengembangkan kemampuan motorik dan bahasa anak usia dini secara holistik. Menggunakan pendekatan kualitatif dengan jenis studi eksploratif deskriptif, penelitian ini dilakukan pada lembaga PAUD yang berada di lingkungan dengan kekayaan budaya lokal yang masih terpelihara. Data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi, serta dianalisis menggunakan teknik analisis tematik. Hasil penelitian menunjukkan bahwa permainan tradisional seperti engklek, congklak, lompat tali, dan permainan peran dari cerita rakyat memiliki karakteristik yang sesuai dengan tahap perkembangan anak, yaitu aktif, kolaboratif, serta mudah dipahami. Permainan ini terbukti mampu menstimulasi keterampilan motorik kasar dan halus melalui aktivitas fisik yang bervariasi, serta meningkatkan kemampuan bahasa anak melalui percakapan, peniruan ungkapan, dan interaksi sosial selama bermain. Temuan ini menegaskan pentingnya integrasi permainan berbasis budaya lokal dalam pembelajaran PAUD sebagai strategi pedagogis yang tidak hanya melestarikan nilai budaya, tetapi juga mendukung tumbuh kembang anak secara menyeluruh.